Ozonolysis at vegetation surfaces:: a source of acetone, 4-oxopentanal, 6-methyl-5-hepten-2-one, and geranyl acetone in the troposphere - Fruekilde, P; Hjorth, J; Jensen, N R (Atmospheric Environment, 1998)
ÐThe present study gives a possible explanation for the ubiquitous occurrence of 6-methyl-5- hepten-2-one and acetone in ambient air and reports for the Þrst time on a widespread occurrence of geranyl acetone and 4-oxopentanal. We have conducted a series of laboratory experiments in which it is demonstrated that signiÞcant amounts of geranyl acetone, 6-methyl-5-hepten-2-one (6-MHO), 4-oxopen- tanal (4-OPA), and acetone are formed by the reaction of ozone with foliage of common vegetation in the Mediterranean area (Quercus ilex'Citrus sinensis'Quercus suber'Quercus freinetto'Pinus pinea). In order to rule out biological formation, epicuticular waxes were extracted from the leaves, dispersed on glass wool and allowed to react with a ßow of artiÞcial air. SigniÞcant amounts of 6-MHO and 4-OPA were formed at ozone concentrations of 50Ð100 ppbv, but not at zero ozone. A number of terpenoids common in vegetation contain the structural element necessary for ozonolytic formation of 6-MHO. Two sesquiter- penes (nerolidol; farnesol), and a triterpene (squalene) selected as representative test compounds were demonstrated to be strong precursors for acetone, 4-OPA, and 6-MHO. Squalene was also a strong precursor for geranyl acetone. The atmospheric lifetime of geranyl acetone and 6-MHO is less than 1 h under typical conditions. For the present study, we have synthesized 4-OPA and investigated the kinetics of its gas-phase reaction with OH, NO 3 , and O 3 . A tropospheric lifetime longer than 17 h under typical conditions was calculated from the measured reaction rate constants, which explains the tropospheric occurrence of 4-OPA. It is concluded that future atmospheric chemistry investigations should included geranyl acetone, 6-MHO, and 4-OPA. In a separate experiment it was demonstrated that human skin lipid which contains squalene as a major component is a strong precursor for the four above-mentioned compounds plus nonanal and decanal. The accidental touching of material which later comes into contact with ozone can lead to strong artifact formation of these carbonyl compounds. Previously published results on these compounds must be seen in this new light
Keywords: epicuticular wax; heterogenous reactions; NO3; O3; OH; products; rate; sesquiterpenes; Squalene